2008
DOI: 10.1080/09540120701506804
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a basic care and prevention package by HIV-infected persons in Uganda

Abstract: Opportunistic infections are the leading cause of mortality among HIV-infected people. Several simple interventions prevent illness, prolong life, or prevent HIV transmission from HIV-infected people in Africa. These include: cotrimoxazole prophylaxis; insecticide-treated bed nets; supplies for household water treatment and safe storage; materials promoting family voluntary counselling and testing (VCT); and condoms. We provided these interventions to adults and children with HIV who were members of the AIDS S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…All source water in study households had organic content that increased chlorine demand, which would effectively eliminate free chlorine residuals in a matter of hours. 18,19 It was also possible that estimates of WaterGuard or PuR ® use were incorrect because the DPD test cannot distinguish between the two products. This is unlikely, however, because all respondents indicated which of the two products they were currently using.…”
Section: Discussionmentioning
confidence: 99%
“…All source water in study households had organic content that increased chlorine demand, which would effectively eliminate free chlorine residuals in a matter of hours. 18,19 It was also possible that estimates of WaterGuard or PuR ® use were incorrect because the DPD test cannot distinguish between the two products. This is unlikely, however, because all respondents indicated which of the two products they were currently using.…”
Section: Discussionmentioning
confidence: 99%
“…Such health care infrastructure facilitates the expansion of other desperately needed health care interventions. One Ugandan study of HIV-infected participants reported that, although 95% of subjects were taking trimethoprim-sulfamethoxazole prophylaxis, many also engaged in concurrently available prevention interventions-89% slept under an insecticide treated bed-net, 65% had current treatment of household drinking water, and 96% reported family use of HIV counseling and testing services [23].…”
Section: Review Of Pepfarmentioning
confidence: 99%
“…Previous health facility-based WASH intervention studies have mostly focused on integrating WASH into clinic-based antenatal services. [28][29][30][31][32][33][34][35] In Kenya, a child and maternal health clinic-based intervention that promoted chlorination of household drinking water as part of regular nursing practice resulted in 71% of households having detectable chlorine in stored drinking water 1 year later. 29 Consistent with this, in Malawi, a health facilitybased water treatment and hygiene intervention integrated into a antenatal program, resulted in 71% of households having detectable chlorine in stored drinking water at the 10-month follow-up, compared with only 9% of households at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are very few published studies that have evaluated the impact of health facility-based WASH interventions for households, and none, to our knowledge, that have evaluated the impact this form of intervention focused on household members of diarrhea patients. [28][29][30][31][32][33][34][35] In an effort to develop a low-cost standard of care for the household members of cholera patients, we recently developed a hospital-based handwashing with soap and water treatment intervention entitled Cholera-Hospital-Based Intervention for 7 days (CHoBI7). In our recent randomized controlled trial (RCT) of this intervention where CHoBI7 was compared with the standard message given in Bangladesh to diarrhea patients at discharge on ORS use, we observed a 47% reduction in the incidence of overall cholera infections (symptomatic and asymptomatic), and a significant reduction in symptomatic cholera infections among household members of cholera cases in the intervention compared with the control arm during the 1 week intervention period.…”
Section: Introductionmentioning
confidence: 99%